Czas wolny mieszkańców województwa pomorskiego w 1945 roku: udział w przedstawieniach - Ławniczak, Remigiusz (Kultura i Społeczeństwo, 2023)
The author describes one form of leisure activity practised by the inhabitants of the Pomeranian Voivodeship in 1945: participation in performances, as broadly understood. Several factors contributed to the interest in this way of spending leisure time: the conditions prevailing in the area under discussion during the Second Polish Republic and the Second World War, and — after the end of the occupation — financial difficulties and the necessity to rebuild culture from scratch. As a consequence, easy and undemanding repertoire enjoyed the greatest popularity. To a large extent, residents lacked the education and capacity to take in works of a more ambitious nature. Archival materials from offices, the press, and the recollections of participants in the events in question were used for the research, along with sociological theories on leisure time, and the function of art and human needs. Due to a lack of data it was not possible to characterize the performances’ audience in greater detail in terms of age, gender, and social background.